2006
DOI: 10.1186/1471-2261-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular geometric patterns in newly presenting nigerian hypertensives: An echocardiographic study

Abstract: BackgroundHypertension is a global problem and it is prevalent in Nigeria. Left ventricular hypertrophy is a major complication of hypertension with risk of sudden death and arrhythmias among others. Abnormal left ventricular geometric patterns also increase the burden of morbidity and mortality. It is therefore important to know the different left ventricular geometric patterns in Nigerian hypertensives because of their prognostic significance.MethodsOne hundred (100) newly presenting hypertensives (53 males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 37 publications
2
23
1
Order By: Relevance
“…In this study abnormal LV geometry was detected in 70% of patients while Aje [11] found 72% of newly diagnosed hypertensive patients to have abnormal LV geometry. Akintunde [12] found abnormal LV geometry in 72% of treated hypertensive patients.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In this study abnormal LV geometry was detected in 70% of patients while Aje [11] found 72% of newly diagnosed hypertensive patients to have abnormal LV geometry. Akintunde [12] found abnormal LV geometry in 72% of treated hypertensive patients.…”
Section: Discussionmentioning
confidence: 71%
“…In this study, the distribution of different abnormal LV geometrical patterns was 19.8%, 28.2%, 22% for concentric remodeling, concentric hypertrophy and eccentric hypertrophy respectively. Aje [11] found the distribution of abnormal LV geometry to be 26%, 28% and 18% for concentric remodeling, concentric hypertrophy and eccentric hypertrophy respectively, while Akintunde [12] found the distribution to be 60.1%, 5.3% and 6.9% for concentric remodeling, eccentric hypertrophy and concentric hypertrophy respectively. The variation can partly be explained by difference in echocardiographic cut-off values for defining LVH and intrinsic population characteristics of a given geographical location.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, a study of 100 newly diagnosed hypertensives by Aje, et al (20) showed that 72% of the patients had abnormal geometric patterns (concentric hypertrophy-28%, concentric remodelling-26%, eccentric hypertrophy-18%). Ogah, et al (21) in another study in Ibadan, Nigeria found that eccentric hypertrophy was the commonest geometric pattern in hypertensives with ECG LVH with strain.…”
Section: Epidemiologymentioning
confidence: 99%
“…Left ventricular (LV) hypertrophy or an increase in the LV mass is a well recognised major complication of systemic hypertension and another important predictor of cardiovascular morbidity and mortality (5,6). In addition, a reduction in the LV mass by antihypertensive treatment reduces the risk for subsequent cardiovascular events.…”
Section: Studies On Aortic Stiffness Left Ventricular Geometry and mentioning
confidence: 99%